CULTURE AND THE HUMANITIES: SYMPTOMATOLOGIES, MOSTLY HISTORICAL, MAINLY GERMAN - Pfeiffer, K. Ludwig (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
Against the backdrop of hermeneutics and German Romanticism, this essay traces the institutional, historical, and conceptual contours of the notion of Geisteswissenschaften. In this context, it concentrates on the conceptions of Kant, Fichte, von Humboldt, and, at greater length, on Dilthey's efforts to use a notion of Geist to meld together life, theory, and the institution. It then plots the transition from a concern with Geist to a concern with Kultur.